2015
DOI: 10.3892/ol.2015.3542
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ALDH1A1 and CD44 in primary head and neck squamous cell carcinoma and their value for carcinogenesis, tumor progression and cancer stem cell identification

Abstract: Abstract. In head and neck squamous cell carcinoma (HNSCC), aldehyde dehydrogenase 1 family, member A1 (ALDH1A1) and hyaluronan receptor cluster of differentiation 44 (CD44) are often used as cancer stem cell (CSC) markers. The aim of the present study was to examine the relevance of these proteins for HNSCC in general and for the identification of CSCs. Tumors from 48 patients with primary HNSCC were analyzed for the expression of ALDH1A1 and CD44. Additionally, the association of the proteins with the prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 36 publications
(30 reference statements)
1
25
0
1
Order By: Relevance
“…Westernblot analysis of representative NPC stem cell markers, ALDH1 and CD44 [ 20 ], revealed increased expression in PTEN−/CNE2 and PTEN−/CNE1 cells, relative to PTEN+ cells (Figure 1C ). As a functional measure of CSCs frequency [ 21 ], we tested the tumorsphere forming ability of PTEN−/+ CNE2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Westernblot analysis of representative NPC stem cell markers, ALDH1 and CD44 [ 20 ], revealed increased expression in PTEN−/CNE2 and PTEN−/CNE1 cells, relative to PTEN+ cells (Figure 1C ). As a functional measure of CSCs frequency [ 21 ], we tested the tumorsphere forming ability of PTEN−/+ CNE2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Our data showed that all markers but ALDH1A1 were increased in HT29-resistant cells. ALDH1A1 expression was undetected in HCT116 parental and drug-resistant cells, although, ALDH1A1 was proposed to characterize a subpopulation of cells with tumor-initiating or cancer stem cell properties in several malignancies (69,70). By contrast with HT29-resistant cells, only CD26 and CD166 showed some increase, but a very limited one, in HCT116/ DocR cells.…”
Section: Discussionmentioning
confidence: 99%
“…In primary head and neck squamous cell carcinoma, the expression patterns of CD44 and EGFR were overlapping and were significantly connected ( 45 ). Although CD44 and EGFR have great impact on the initiation and progression of breast cancer, whether there was any connection between CD44 and EGFR still lacks direct evidence in breast cancer.…”
Section: Discussionmentioning
confidence: 99%